Tourism Sector Strategy for Increasing GRDP in Batam City in the New Normal Era - Lily Indrawati; Irine Lim; Angeline Goh; Wulandari Ginting; Liani Lilik (Green Publisher Indonesia, 2021)
The Batam City Government continues to try to revive the tourism sector which continues to weaken due to the Covid-19 pandemic. Therefore, a well-targeted strategy is needed to be implemented, of course, in accordance with health protocols during the pandemic and towards the new normal era. This study uses qualitative secondary data considering the Covid situation and current health protocol regulations do not allow primary data collection. The sources studied are in the form of recorded and published data, both in the form of books, research reports, journals, as well as data published by the Central Statistics Agency, the Culture and Tourism Office, the Health Office, the Batam City Communication and Information Office and other supporting data. , including the rules and regulations of the relevant agencies. The results of this study conclude that the efforts that have been made by the Batam city government to revive the tourism sector are still in the form of cultural arts events that have been scheduled to be held throughout 2021 and infrastructure development and city planning to make the city more beautiful, attractive, and instagramable. However, public awareness regarding the importance of adherence to health protocols is still not optimal.